2013
DOI: 10.1007/s00264-013-2053-8
|View full text |Cite
|
Sign up to set email alerts
|

Do we really need closed-suction drainage in total hip arthroplasty? A meta-analysis

Abstract: Purpose The clinical use of closed-suction drainage, which aims to reduce postoperative wound haematomas and infection, is common. This study was performed to determine whether closed-suction drainage is safe and effective in promoting wound healing and reducing blood loss and other complications compared with no-drainage in total hip arthroplasty. Methods The literature search was based on PubMed, the Cochrane Library, MEDLINE, and EMBASE. The data were evaluated using the generic evaluation tool designed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 25 publications
3
54
0
3
Order By: Relevance
“…However, there is some evidence that closed-suction drains in THA increase blood transfusion [32]. Johansson et al [33] found in a prospective, randomized controlled trial that wound compressions reduce wound discharge, and transfusion rates compared to drainage after THA.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence that closed-suction drains in THA increase blood transfusion [32]. Johansson et al [33] found in a prospective, randomized controlled trial that wound compressions reduce wound discharge, and transfusion rates compared to drainage after THA.…”
Section: Discussionmentioning
confidence: 99%
“…However, CSD has been shown to be associated with increased blood loss by eliminating the tamponade effect produced by haematoma formation and may allow for retrograde dissemination of skin bacteria into the joint space [9]. A recent meta-analysis of 3,186 patients undergoing primary THA showed that the use of CSD increased the rate of blood transfusion and did not provide any benefits regarding to the incidence of infection, functional recovery or other complications [10].…”
Section: Introductionmentioning
confidence: 97%
“…3 For hip and knee arthroplasty, several studies have shown no difference in the incidence of infection, blood loss, changes in hemoglobin and hematocrit, functional assessment, or other complications when the drainage group was compared with the no-drain group. 48 In orthopaedic trauma studies, drains have also been found to be unnecessary. 9,10 …”
Section: Introductionmentioning
confidence: 99%